2019
DOI: 10.1002/rra.3408
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprinting the contribution of quarrying to fine‐grained bed sediment in a mountainous catchment, Iran

Abstract: The contribution of quarrying in the context of multiple catchment sources of fine‐grained sediment has rarely been investigated. This study assessed the relative importance of quarrying as a sediment source alongside rangeland surface soils and channel banks in a mountainous catchment in northern Tehran, Iran, using fingerprinting. Eight geochemical tracers were measured on 24 potential sediment source samples and four fine‐grained sediment samples. Statistical analysis to select three different composite fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…Except in the 125-250 µm fraction for both the weathering indices only and a combination of the geochemical elements and weathering indices, the errors were acceptable for all other fractions. Similar ndings have been reported by studies applying sediment source ngerprinting in both uvial and aeolian systems 23,51,52 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Except in the 125-250 µm fraction for both the weathering indices only and a combination of the geochemical elements and weathering indices, the errors were acceptable for all other fractions. Similar ndings have been reported by studies applying sediment source ngerprinting in both uvial and aeolian systems 23,51,52 .…”
Section: Discussionsupporting
confidence: 89%
“…The Modi ed MixSIR Bayesian model was used to apportion the aeolian sediment source contributions. This model has been mainly used in sediment source tracing studies in uvial systems [48][49][50][51] , but more recently in aeolian and storm dust source tracing 19 . The model was run for 10 6 iterations with the nine different nal composite ngerprints generated based on the different combinations of tracers.…”
Section: Sand Dune Source Discrimination and Apportionmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The RMSE results showed that 15 of 30 possible predicted values were < 10%, whilst in the case of MAE, 29 of the 30 values were < 10%. These error levels were judged to be acceptable in the context of those reported elsewhere in the international literature (e.g., Haddadchi et al, 2013; Nosrati and Collins, 2019; Palazón et al, 2015).…”
Section: Resultsmentioning
confidence: 91%
“…The Modi ed MixSIR Bayesian model was used to apportion the aeolian sediment source contributions. This model has been mainly used in sediment source tracing studies in uvial systems [48][49][50][51] , but more recently in aeolian and storm dust source tracing 19 . The model was run for 10 6 iterations with the nine different nal composite ngerprints generated based on the different combinations of tracers.…”
Section: Sand Dune Source Discrimination and Apportionmentmentioning
confidence: 99%